Determinants of knowledge, attitude, and practice towards aflatoxin contamination in food and aflatoxin biomarker levels among healthy Malaysian adults - Chang, Wei Lin; Jamaluddin, Rosita; Abu Saad, Hazizi; Sabran, Mohd Redzwan (Malaysian Journal of Nutrition, 2024)
Limited information exists regarding the factors that determine the levels of knowledge, attitude, and practice (KAP) towards aflatoxin contamination in food, including aflatoxin biomarker levels in populations at risk. This study examined the associations between KAP levels with sociodemographic characteristics and weight status of 359 healthy Malaysian adults. The study was conducted among residents and workers in Selangor, Malaysia. Sociodemographic characteristics and KAP levels were collected using a self-administered questionnaire, and body weight was measured. Urine and fasting blood samples were collected for aflatoxin M1 and aflatoxin B1 analyses, respectively. Most respondents were females, Chinese, aged 25–44 years, with poor knowledge but positive attitudes and acceptable practices in controlling aflatoxin contamination in food. Univariate and multivariate analyses revealed that the knowledge level was remarkably high among females, unemployed, underweight or normal weight individuals, and those with a monthly income of >RM 10,000. The attitude score was high in those with tertiary education and those who were unemployed, while the practice score was high in those with tertiary education. The levels of aflatoxin biomarkers varied significantly according to ethnicity or age. These findings demonstrated that sociodemographic characteristics and body weight status partly determined the levels of KAP and aflatoxin biomarkers; this may aid in identifying populations that would benefit from educational interventions to prevent aflatoxin contamination.